Designing a Resilience Program for Critical Care Nurses. (2017) - Mealer, Meredith; Hodapp, Rachel; Conrad, David; Dimidjian, Sona; Rothbaum, Barbara O.; Moss, Marc
Abstract : Background: Workplace stress can affect job satisfaction, increase staff turnover and hospital costs, and reduce quality of patient care. Highly resilient nurses adapt to stress and use a variety of skills to cope effectively. Objective: To gain data on a mindfulness‐based cognitive therapy resilience intervention for intensive care unit nurses to see if the intervention program would be feasible and acceptable. Methods: Focus‐group interviews were conducted by videoconference with critical care nurses who were members of the American Association of Critical‐Care Nurses. The interview questions assessed the feasibility and acceptability of a mindfulness‐based cognitive therapy program to reduce burnout syndrome in intensive care unit nurses. Results: Thirty‐three nurses participated in 11 focus groups. Respondents identified potential barriers to program adherence, incentives for adherence, preferred qualifications of instructors, and intensive care unit‐specific issues to be addressed. Conclusions: The mindfulness‐based cognitive therapy pilot intervention was modified to incorporate thematic categories that the focus groups reported as relevant to intensive care unit nurses. Institutions that wish to design a resilience program for intensive care unit nurses to reduce burnout syndrome need an understanding of the barriers and concerns relevant to their local intensive care unit nurses.